Information as a subject in law and in information science: A comparative study based on the Brazilian reality - Santos, João Carlos Gardini [UNESP]; Guimarães, José Augusto Chaves [UNESP]; Fernández-Molina, Juan-Carlos (My University, 2018)
This paper seeks to delineate the extent to which the concept of information is presented in the areas of Law and Information Science in Brazil, seeking to identify descriptive features in their convergent and complementary aspects. For this, a literature review on the subject followed by the application of the content analysis methodology (Bardin, 2009) was carried out based on the categories processes, objectives, elements, features and rights arising from the information. The results reveal a convergence between the Law and the Information Science in aspects related to the act of informing or informing someone, the transmission of knowledge as the objective of the information and the need for a support to give materiality to the information. In the case of Information Science, there is a greater emphasis on the informational processes of production, organization and use of information and its conceptual dimensions (as knowledge, as a process and as a thing). In the case of Law, the emphasis is on the effects or guarantees arising from access to information and the legal principles inherent in the right of information (for example, non-disclosure, publicity, universality etc.). It can be concluded that the increasingly technical use of the term in Law requires the theoretical reference of Information Science, so that its conceptual dimension can be delimited more specifically, with a view to the sedimentation of its terminology.
A informação como assunto no direito e na ciência da informação: Um estudo comparativo a partir da realidade brasileira
Keywords: Access to information act; Content analysis; Information; Information organization; Legal information